PENGEMBANGAN KETERAMPILAN GURU DALAM MENGIDENTIFIKASI KARAKTERISTIK DAN GAYA BELAJAR SISWA UNTUK MENDESAIN INSTRUKSI PEMBELAJARAN - Cahyono, Rudi; Hendriani, Wiwin; Wulandari, Primatia Yogi (Jurnal Abdi Insani, 2024)
Teachers have a very crucial role in the success of learning in schools. The reality that often occurs in the field is that the main problem faced by teachers is their low ability to facilitate learning that suits students’ characteristics and learning styles. Most teachers do not know how to identify students’ characteristics and learning styles, and use these uniqueness to create or adjust learning designs. This was also experienced by the Miftahul Hikmah Sidoarjo Flagship School. Based on these needs, this community service activity is aimed at providing training to develop teacher skills in identifying and using students’ characteristics and learning styles to design or adapt instructional learning designs. The methods used in this program are focus group discussions, training and mentoring. Participants in this program were 20 teachers from the Madrasah Ibtidaiyah Miftahul Hikmah Sidoarjo as a prototype. This activity will be continued in several elementary schools/madrasahs in Sidoarjo Regency. The result of this activity was an increase in teachers’ ability to identify students’ characteristics and learning styles using The Multiple Intelligence, Myer-Briggs Type Indicator (MBTI) and Learning Style approaches. Meanwhile, to identify learning styles using visual, auditory and kinesthetic concepts. Apart from identifying individual students, teachers could also identify the characteristics and learning styles of classes (group of students). In addition, participats could adjust teaching modules based on student characteristics and learning styles. Teachers could identify components of teaching modules that could be adjusted based on the results of identifying students’ characteristics and learning styles, as well as being able to adapt teaching modules.